2020
DOI: 10.1002/ijc.32894
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of hsa‐miR‐16‐5p, hsa‐miR‐29a‐3p, hsa‐miR‐150‐5p, hsa‐miR‐155‐5p and hsa‐miR223‐3p and subsequent risk of chronic lymphocytic leukemia in the EPIC study

Abstract: Serum levels of hsa-miR-16-5p, hsa-miR-29a-3p, hsa-miR-150-5p, hsa-miR-155-5p and hsa-miR-223-3p and subsequent risk of chronic lymphocytic leukemia in the EPIC study

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 49 publications
1
17
0
Order By: Relevance
“…TCL1 induces AKT activation and inhibits DNA methyltransferases Dnmt3A and Dnmt3B, reducing DNA methylation in CLL cells [173,174]. MiR-29 family deregulation has been specially revealed in exosomes from plasma of CLL patients, as mentioned above [51], and could therefore be employed as a useful biomarker for CLL diagnosis and progression. However, a recent study showed that all miR-29 family members (miR-29a, miR-29b, and miR-29c) were consistently downregulated in the CLL microenvironment as a consequence of BCR activation and seemed to correlate with a significantly shorter overall survival of CLL patients.…”
Section: Chronic Lymphocytic Leukemiamentioning
confidence: 96%
See 1 more Smart Citation
“…TCL1 induces AKT activation and inhibits DNA methyltransferases Dnmt3A and Dnmt3B, reducing DNA methylation in CLL cells [173,174]. MiR-29 family deregulation has been specially revealed in exosomes from plasma of CLL patients, as mentioned above [51], and could therefore be employed as a useful biomarker for CLL diagnosis and progression. However, a recent study showed that all miR-29 family members (miR-29a, miR-29b, and miR-29c) were consistently downregulated in the CLL microenvironment as a consequence of BCR activation and seemed to correlate with a significantly shorter overall survival of CLL patients.…”
Section: Chronic Lymphocytic Leukemiamentioning
confidence: 96%
“…A recent study investigated whether serum levels of miRNAs can be used as a predictive biomarker of CLL. It was found that miR-29a, miR-150-5p, and miR-155-5p were upregulated in the early stages of CLL, but that these miRNAs were poor predictive biomarkers of CLL risk [51].…”
Section: Circulating Mirnasmentioning
confidence: 99%
“… TB Premix Ex Taq [ 32 ] Lung cancer 40 pairs of tumor tissues and ANCTs Upregulation in Linc00210 (which sponges miR-16-5p) SYBR Premix Ex Taq II and Perfect Real Time [ 34 ] 31 pairs of tumor tissues and ANCTs Upregulation in XIST (which sponges miR-16-5p) SYBR Green Master Mix [ 35 ] Colorectal cancer 72 pairs of tumor tissues and ANCTs Upregulation in PVT1 (which sponges miR-16-5p) Lower OS Upregulation in PVT1 was significantly correlated with lymph node metastasis, distant metastasis, and TNM (tumor, node, metastasis) stage SYBR Green [ 36 ] 42 pairs of tumor tissues and ANCTs Upregulation in ALDH1A3 (a target of miR-16-5p) Lower OS [ 37 ] GEO database: GSE75970, GSE74602, GSE89076, and GSE10950 Upregulation in ITGA2 (a target of miR-16-5p) [ 38 ] Chronic lymphocytic leukemia 224 CLL cases and 224 matched controls miR-16-5p levels were unrelated to CLL risk. TaqMan probes [ 49 ] Chondrosarcoma 9 human chondrosarcoma tissues and 9 normal cartilage Downregulation in miR-16-5p [ 42 ] Giant cell tumor of bone …”
Section: Introductionmentioning
confidence: 99%
“…Leukemia and lymphoma are malignant tumors, having complicated etiology, in whose development and progression miRNAs and benzene exposure play roles. MiRNAs can act as oncogenes in the initiation and progression of leukemia and lymphoma, such as miR‐223, miR‐155, [ 26 ] miR‐146a, [ 27 ] and miR‐125. [ 28–31 ] MiR‐223 is a hematopoietic lineage cell‐specific miRNA, [ 32 ] it regulates NFI‐A, [ 33 ] E2F1, [ 34 ] and IKK‐α [ 35 ] in leukemia via binding to their 3′‐untranslational regions.…”
Section: Introductionmentioning
confidence: 99%